NATO Defense Posture in an Environment of Strategic Parity and Precision Weaponry - Kennedy, Robert (1976)
The advent of a rough strategic and theater nuclear parity and the continued buildup of Warsaw Pact conventional capabilities have resulted in new perceptions concerning the balance of arms in central Europe. This memorandum considers two schools of thought which have gained prominence in their attempts to forge a more credible defense posture for NATO: those who support a conventional-emphasis strategy; and those who contend that a policy which emphasizes the early use of nuclear weapons can provide the only sound basis for credible deterrence and effective defense in Western Europe. The author concludes that only through the development of force postures which provide NATO with both an effective conventional deterrent and defense against conventional aggression, and an effective theater nuclear deterrent and defense as a counter to nuclear aggression, can the West hope to ameliorate the psychological effect of Soviet conventional and nuclear forces which threaten the undermining of the North Atlantic Alliance.